Food system institutional mapping and capacity assessment in Niger - Srivastava, Nandita; Hema, Aboubacar; Babu, Suresh Chandra; Ulimwengu, John M.; Benin, Samuel (International Food Policy Research Institute, 2025)
Niger faces rampant food insecurity, malnutrition, and environmental degradation. The transformation of food systems to tackle such challenges hinges on the capacity and effectiveness of institutional frameworks. To analyze the status, challenges, and strengths of Niger’s food system, a mapping and capacity needs assessment was conducted at three levels—enabling environment, institutional, and individual. Based on the assessment, leadership concerns on strategic guidance were observed at the policy process level, with major issues such as the incidence of corruption, infrastructure constraints, and lack of reliable data availability. At the institutional level, lack of an interconnected network and mutual accountability, resource and funding constraints, and high staff turnover have adversely impacted overall institutional performance. Availability of reliable data evidence is limited or absent due to weak monitoring and evaluation systems and decentralized capacity, lack of sufficient local support, transparency issues in strategy development, and selection bias. At the individual level, there is a need to improve technical capacity on analytical thinking, quantitative and qualitative research tools, and the dissemination of communication, outreach, and information. Despite the climate change-related challenges in the country, there is less focus on environmental management, adaptation, and advanced technology implementation. The underrepresentation of key areas such as socio-cultural dynamics, governance, social protection, and cross sectoral collaboration indicates a potential lack of integration in policymaking and implementation. Overall, there is an urgent need to reallocate resources to enhance the focus on underrepresented yet critical food systems areas, enhance inter-ministerial and cross-sectoral collaboration to ensure a more integrated approach to food systems management, and incorporate social inclusion and equity considerations. Forward-looking strategies should be developed that anticipate and respond to emerging challenges such as demographic shifts, globalization effects, and technological changes.